Infectious Complications in Critically Ill Liver Failure Patients - Cheung, Amanda; Tanna, Sajal; Ison, Michael G. (Seminars in Respiratory and Critical Care Medicine, 2018)
Infections remain a leading cause of morbidity and mortality among patients with liver failure. A number of factors, including relative immune dysfunction and systemic inflammation, bacterial translocation, gut dysbiosis, small intestine bacterial overgrowth, altered bile acid pools, and changes in pH due to acid suppression, contribute to the high rates of infection in this population. Though a range of infections can complicate the course of cirrhotic patients, spontaneous bacterial peritonitis (SBP), cholangitis, and cholecystitis in addition to other infections (i.e. pneumonia, urinary tract infection, bacteremia, and Clostridioides difficile colitis) are more common in this population and will be reviewed in this article. Preventative strategies are directed at minimizing the risk of SBP through the use of targeted antimicrobial prophylaxis. Lastly, the critically ill cirrhotic patient may present with an acute need for liver transplantation. Thus, careful assessment for ongoing infection should be performed and treated to optimize outcomes of transplant, if needed.
Keywords: cirrhosis; spontaneous bacterial peritonitis; cholangitis; cholecystitis; pneumonia; UTI; bacteremia and C. difficile colitis